The cholera epidemic of 2000/2001 in Kwazulu-Natal: implications for health promotion and education - A KM Hoque; Zeleke Worku (AOSIS, 2005)
This study was a cross-sectional, descriptive and comparative study conducted in the province of KwaZulu-Natal in the months of November and December 2001 in order to make a comparison between health districts stricken with cholera and districts not stricken with cholera with regards to well-known risk factors for cholera. Opsomming 'n Dwarssnit, beskrywende en vergelykende studie met verwysing na bekende risikofaktore vir cholera het in die KwaZulu-Natal Provinsie tussen November en Desember 2001 plaasgevind om 'n vergelyking te maak tussen gesondheidsdistrikte wat deur cholera geteister word en distrikte wat nie deur cholera geteister word nie. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.